Modern cities modelled as “super‐cells” rather than multicellular organisms: Implications for industry, goods and services - Chang, Jie; Ge, Ying; Wu, Zhaoping; Du, Yuanyuan; Pan, Kaixuan; Yang, Guofu; Ren, Yuan; Heino, Mikko P.; Mao, Feng; Cheong, Kang Hao; Qu, Zelong; Fan, Xing; et al. (BioEssays, 2021)
Abstract The structure and “metabolism” (movement and conversion of goods and energy) of urban areas has caused cities to be identified as “super‐organisms”, placed between ecosystems and the biosphere, in the hierarchy of living systems. Yet most such analogies are weak, and render the super‐organism model ineffective for sustainable development of cities. Via a cluster analysis of 15 shared traits of the hierarchical living system, we found that industrialized cities are more similar to eukaryotic cells than to multicellular organisms; enclosed systems, such as factories and greenhouses, paralleling organelles in eukaryotic cells. We further developed a “super‐cell” industrialized city model: a “eukarcity” with citynucleus (urban area) as a regulating centre, and organaras (enclosed systems, which provide the majority of goods and services) as the functional components, and cityplasm (natural ecosystems and farmlands) as the matrix. This model may improve the vitality and sustainability of cities through planning and management.